The Constitutional Court: law, equality and suspicious categories - Ortiz Custodio, José David (Iuris Dictio, 2018)
This article provides an account of the precedents issued by the Constitutional Court of Ecuador regarding the right to equal protection of the laws. Since the Constitutional Court has referred to standards of review developed by the Supreme Court of the United States to determine whether differentiations in law comply with the equal protection clause of the fourteenth amendment of the U.S. Constitution, I will provide a brief overview of the equal protection case law and analyze the relevant criteria to consider a class as suspect. Finally, this article will demonstrate that the Constitutional Court precedents concerning suspect categories and levels of scrutiny must be corrected, since its application in concrete cases will be problematic for lower level courts.